The Chiquerío Formation, southern Peru - Chew, D.; Kirkland, Chris (2011)
The Chiquerío Formation (Fm.) is a thick glaciogenic succession deposited unconformably on gneisses of the Arequipa massif in southern Peru. It has undergone greenschist facies metamorphism during Early Palaeozoic orogenesis. The Chiquerío Fm. consists of nearly 400 m of diamictite, sandstone, mudstone and carbonate, with a thin (11 m) cap dolostone at the top of the formation. It is overlain by the San Juan Fm., a 2-km-thick carbonate succession. The thick glacially influenced succession was deposited in deep marine conditions and consists mainly of massive diamictites (representing either ice-rafted debris or submarine debris flows) interbedded with turbiditic sandstones. Where internal lamination is present (e.g. bedding in the turbiditic packages), abundant dropstones can be recognized. There is no evidence of shallow marine reworking of the succession. No absolute age constraints on the depositional timing of the Chiquerío Fm. exist, because no volcanic tuffs have yet been identified. U–Pb dating of detrital zircons (U–Th–Pb SIMS) from the Chiquerío Fm. and the overlying San Juan Fm. suggest it is autochthonous with respect to Amazonia, as the detrital zircon age spectra suggest derivation from the Amazonian craton. Detrital grains as young as c. 700 Ma have been documented in the post-glacial San Juan Fm. The sparse (chemo)stratigraphic data available for the Chiquerío Fm. exhibit patterns similar to those observed generally in Neoproterozoic post-glacial carbonate sequences. Palaeogeographic models for the deposition of the Chiquerío Fm. are critically dependent on the timing of the docking of the basement of the Arequipa massif with the South American craton (Amazonia). Presently there are no palaeomagnetic constraints. More research on the chronological and palaeogeographical constraints of this succession is required.